Problem of conjugate heat transfer between main gas pipeline and frozen ground - Bondarev Edward; Rozhin Igor; Argunova Kira (E3S Web of Conferences, 2019)
Mathematical model of non-isothermal gas flow within the framework of tube hydraulics including change of tube cross-section due to hydrate formation and the dependence of coefficient of heat transfer between gas and hydrate layer on varying flow area is proposed. The corresponding conjugate problem of heat exchange between imperfect gas in the pipeline and the environment is reduced to the solution of differential equations describing non-isothermal flow of gas in pipes and heat transfer equations in ground with the corresponding conjugation conditions. In the quasi-stationary mathematical model of hydrate formation (dissociation), the dependence of gas-hydrate transition temperature on gas pressure is taken into account. Some decisions taken in the design of the first section of the main gas pipeline «Power of Siberia» have been analyzed. It has been shown that if gas is not sufficiently dried, outlet pressure may drop below the technological limit in about 6-7 hours. At the same time, for completely dry gas ,it is possible to reduce the cost of thermal insulation of the pipeline at least two fold.